Formulation and Stability of Ataluren Eye Drop Oily Solution for Aniridia - Celia Djayet; Dominique Bremond-Gignac; Justine Touchard; Philippe-Henri Secretan; Fabrice Vidal; Matthieu P. Robert; Alejandra Daruich; Salvatore Cisternino; Joël Schlatter (MDPI AG, 2020)
Congenital aniridia is a rare and severe panocular disease characterized by a complete or partial iris defect clinically detectable at birth. The most common form of aniridia occurring in around 90% of cases is caused by PAX6 haploinsufficiency. The phenotype includes ptosis, nystagmus, corneal limbal insufficiency, glaucoma, cataract, optic nerve, and foveal hypoplasia. Ataluren eye drops aim to restore ocular surface PAX6 haploinsufficiency in aniridia-related keratopathy (ARK). However, there are currently no available forms of the ophthalmic solution. The objective of this study was to assess the physicochemical and microbiological stability of ataluren 1% eye drop in preservative-free low-density polyethylene (LDPE) bottle with an innovative insert that maintains sterility after opening. Because ataluren is a strongly lipophilic compound, the formulation is complex and involves a strategy based on co-solvents in an aqueous phase or an oily formulation capable of totally dissolving the active ingredient. The visual aspect, ataluren quantification by a stability-indicating chromatographic method, and microbiological sterility were analyzed. The oily formulation in castor oil and DMSO (10%) better protects ataluren hydrolysis and oxidative degradation and permits its complete solubilization. Throughout the 60 days period, the oily solution in the LDPE bottle remained clear without any precipitation or color modification, and no drug loss and no microbial development were detected. The demonstrated physical and microbiological stability of ataluren 1% eye drop formulation at 22-25 °C might facilitate clinical research in aniridia.